Distribution and biology of the colossal squid, Mesonychoteuthis hamiltoni: New data from depredation in toothfish fisheries and sperm whale stomach contents. (May 2019) - Remeslo, Alexander; Yukhov, Valentin; Bolstad, Kathrin; Laptikhovsky, Vladimir
Abstract: We provide new insights into the biology and distribution of the colossal squid (Mesonychoteuthis hamiltoni), by analysing historical data collected during the commercial whaling years (1967–1974) together with recent information collated by CCAMLR observers in 2012–2017. The maximum abundance of colossal squid has been observed in the Indian Ocean sector of the Antarctic (Cooperation Sea), and the lowest in the Ross Sea (the area of highest abundance of its predator and competitor, the Antarctic toothfish, Dissostichus mawsoni ). The colossal squid appears to feed primarily on mesopelagic fish. Spawning likely occurs in summer; ovulation is synchronous and mature egg size is ∼3 mm. Adult (large and maturing) M. hamiltoni are the most abundant in sperm whale diets at surface temperatures of −0.9 to 0 °C, which may indicate the locations of spawning grounds. Highlights: The maximum abundance of colossal squid occurs in the Cooperation Sea and the lowest in the Ross Sea. Spawning likely occurs in summer; ovulation is synchronous and mature egg size is ∼3 mm. The colossal squid feed primarily on mesopelagic fish, neither cephalopod not krill found in stomachs.